Issues and challenges in wakaf seetee aishah property development, Penang state Islamic religious council (MAINPP) - Ismail, Sukriah; Bakar, Marina Abu; Ismail, Che Zuina; Ramli, Noor Asyimah (Linguistics and Culture Review, 2021)
The Penang Islamic Religious Council (MAINPP) is a major leader in the development of waqf properties, especially through its inaugural product Wakaf Seetee Aisah. In managing the assets of the ummah, of course, MAINPP goes through various twists and challenges in order to implement the dreams of waqf givers and develop the socio -economy of the community. This study focuses on the issues and challenges of Seetee Aisah Wakaf Development and further suggests some improvements for the development of waqf land by MAINPP. Qualitative study using the method of interviews with parties involved in the development of endowment properties in MAINPP. The results of the study found that MAINPP faces several challenges in developing waqf properties. Therefore, to address the challenges faced, it is proposed that MAINPP improve the development mechanism for waqf properties to be in line with the vision and mission of MAINPP. Thoroughly, this study provides added value to MAINPP and the parties involved in facing the challenge of developing waqf properties in Malaysia.